OPP approach for multi degree of freedom robotic arm Based on Kinematics and Dynamics of Robot - Praneet Dutta; Rashmi Ranjan Das; Rupali Mathur; Deepika Rani Sona (Institute of Advanced Engineering and Science, 2015)
This paper deals with the trajectory and path generation of the industrial manipulator. The trajectory is obtained using the equations of motion and also the optimal path planning (OPP) approach under kinodynamic constraints. The optimal control problem is defined for the minimum cost function and to obtain the necessary conditions. Here we have used pontrygain’s minimum principle to obtain the limiting value of joint angle and also the joint velocity and torque. In this paper we have used the “Two degree of freedom (DOF) manipulator” for analysis and designing the optimal control for multi link and multi degree of freedom manipulator. For analysis purposes, simulation software has been used to formulate the trajectory and minimize the cost function involved.